DEVELOPING A MEDIA BOOK CREATOR FOR INTENSIVE READING BASED ON LOCAL WISDOM FOR ENGLISH STUDY PROGRAM STUDENTS - Tuminah, Tuminah; Nurcahyoko, Kunto; Giovani, Wanda (English Review: Journal of English Education, 2024)
Rapid advancements in science and technology over the past decade have greatly influenced the development of teaching materials. This accelerated progress has provided significant support to educators in enhancing the quality of both online and offline learning experiences. This study aims to develop a local wisdom-based book creator media while assessing its validity, effectiveness, and innovativeness.The research methodology employed a research and development (R&D) approach, specifically following the procedure outlined by Borg and Gall, which consists of 10 stages. However, this study focused on 8 key stages within the development process. The findings of this research indicate that the local wisdom-based book creator media demonstrate a high level of feasibility. A questionnaire was employed as the primary data collection technique to evaluate the feasibility of the media book creator. Expert assessments were obtained from media experts, material experts, and IT experts, while feedback from lecturers and students also contributed to the evaluation process. The results show that media experts evaluated it at 90%, material experts at 93%, IT experts at 95%, and student responses indicated an 85% feasibility rating, collectively suggesting the learning media to be "highly feasible" for implementation. Educators can leverage this medium to provide students with a more interactive and culturally relevant learning experience, fostering a deeper connection between academic content and their local contexts.